A study on conceptual metaphors in “nỗi buồn chiến tranh” by bao ninh and their english translational equivalents - Hoàng, Thị Thủy (ĐHĐN., 2015)
This study aims at conducting a contrastive analysis of conceptual metaphors in “Nỗi Buồn Chiến Tranh” by Bao Ninh and their English translational equivalents in “The Sorrow Of War” by Frank Palmos and Phan Thanh Hao. The data for analysis were taken from the two versions with 108 samples in Vietnamese and 85 samples in English. The qualitative and quantitative approaches are exploited to help the researcher achieve the aims and the objectives proposed. The results of the investigation have pointed out nine conceptual metaphors of two versions, loss and gain in translation of conceptual metaphors, the frequency of conceptual metaphors in “Nỗi Buồn Chiến Tranh” and its English version as well as the similarities and differences in using metaphors between two versions. The differences between Vietnamese and English made great changes in meaning of metaphorical expressions in translation process. In fact, there are 35 cases of disappearance of metaphors, 20 cases of loss in meaning and 23 cases of gain in meaning. As a result, English equivalents have smaller rate of frequency than their Vietnamese originals. However, in general, the English version “The Sorrow Of War” remains fully the original story. This research is carried out in order to give more understanding for conceptual metaphors in two versions. Moreover, making a contribution to the variety of conceptual metaphors is also our desire. The implications of the thesis can be a useful reference for those who are interested in teaching and learning conceptual metaphors.